Molecular typing of Treponema pallidum in the Czech Republic during 2011 to 2013: increased prevalence of identified genotypes and of isolates with macrolide resistance - Grillová, Linda; Pĕtrošová, Helena; Mikalová, Lenka; Strnadel, Radim; Dastychová, Eliška; Kuklová, Ivana; Kojanová, Martina; Kreidlová, Miluše; Vaňousová, Daniela; Hercogová, Jana; Procházka, Přemysl; Zákoucká, Hana; et al. (Journal of clinical microbiology, 2014)
From January 2011 to December 2013, a total of 262 samples, from 188 patients suspected of having syphilis were tested for the presence of treponemal DNA by PCR amplification of five chromosomal loci, including the polA (TP0105), tmpC (TP0319), TP0136, TP0548, and 23S rRNA genes. Altogether, 146 samples from 103 patients were PCR positive for treponemal DNA. A set of 81 samples from 62 PCR-positive patients were typeable, and among them, nine different genotypes were identified. Compared to a previous study in the Czech Republic during 2004 to 2010, the number of genotypes detected among syphilis patients in a particular year increased to six in both 2012 and 2013, although they were not the same six. The proportion of macrolide-resistant clinical isolates in this 3-year study was 66.7%.
Keywords: molekulární typizace; Macrolides; Male; RNA, Ribosomal, 23S; Prevalence; Syphilis; genotyp; Drug Resistance, Bacterial; Humans; makrolidy; DNA bakterií; Molecular Typing; DNA, Bacterial; Genes, Bacterial; RNA ribozomální 23S; Czech Republic; Česká republika; mužské pohlaví; bakteriální geny; prevalence; Female; syfilis; genetická variace; ženské pohlaví; Anti-Bacterial Agents; Treponema pallidum; Adult; bakteriální léková rezistence; dospělí; lidé; antibakteriální látky; Genotype; Genetic Variation